THE INFLUENCE OF SOCIAL MEDIA ON ENGLISH LANGUAGE DEVELOPMENT - Behruzkhon Yuldoshev Behzod ugli (FANLARARO TAFAKKUR MAVZUSIDAGI ILMIY-AMALIY KONFERENSIYA, 2025)
This article examines how social media influences English language development among learners and users worldwide. The widespread use of digital platforms such as Facebook, Instagram, TikTok, Twitter (X), and YouTube has transformed the ways in which people learn, practice, and interact in English. Social media encourages informal language acquisition through exposure, communication, and content creation. While it provides rich opportunities for language learning beyond the classroom, it also presents challenges such as informal grammar use, slang adoption, and limited accuracy. The paper discusses both the positive and negative impacts of social media on English language learning and development.